GAMBARAN PERILAKU BULLYING ANAK USIA 10-15 TAHUN DI DESA GUNAKSA KLUNGKUNG - Nur Syawali, Ariani; Wahyuni, Ni Putu Elvira Francis; Hastuti, Ni Komang Sri; Sulistiowati, Ni Made Dian; Diana Diantari, Desak Ayu (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p01, 2024)
Bullying is violent behavior that continuously abuses power against someone who is felt to be weaker and more helpless. The aim of this research is to determine the description of bullying behavior of students aged 10-15 years in Gunaksa Village. This type of research is analytical descriptive with a survey approach. This research was conducted on July 18, 2023. The population of this research was 185 students aged 10-15 years using Stratified random sampling technique. The data collection tool uses the OBVQ questionnaire (The Revised Olweus Bully/Victim Questionnaire). Data analysis used univariate analysis using frequency distribution. The results of the research showed that 141 students aged 10-15 years in Gunaksa categorized as positive bullying attitudes (76,2%). Therefore, it is necessary to monitor children's activities and handle bullying cases by the parties involved, namely the school, parents and health workers.